Impact of Leverage on Corporate Profitability A Study on Listed Financial Sector in Sri Lanka - Tharshiga, P.; Subramaniam, V.A.; Anandasayanan, S. (University of Jaffna, 2013)
In finance, Leverage in the extent or degree to which the company total capital is composed of debt financing which increase overall risk and return of the company. Leverage is a technique for magnify gains and losses. This present study empirically investigated the relationship between leverage and profitability of financial sector of Sri Lanka, by using five years data (2008-2012) extracted from the financial statements of the fifteen companies listed on Colombo stock exchange. Hypotheses were formed and results were analyzed through correlation and regression analysis. Based on the results degree of operating leverage (DOL), degree of financial leverage (DFL) and degree combined leverage (DCL) had significantly impact of return on Assets (ROA) and return on equity (ROE).financial industries have to pay more attention on leverage. While leverage magnifies profits when the returns from the asset more than offset the costs of borrowing, losses are magnified when the opposite is true.
Keywords: Operating leverage; Financial Leverage; Profitability